Optimizing Student Potential Through 21st Century Learning Based on Multiple Intelligences - Rudiana Rudiana (UIN Sunan Gunung Djati Bandung, 2025)
Education is the foundation of societal progress, as only communities with strong awareness and high levels of education can produce quality human resources. Effective learning processes are essential to optimize students’ potential. This study employs a qualitative approach through library research. Findings reveal that a knowledge-based society represents the peak of 21st-century development. In this era, human resources must be literate not only in reading, writing, and arithmetic, but also in digital skills, politics, social systems, and history. Continuous knowledge accumulation requires the ability to “learn how to learn.” Managing this ability involves learning through one’s best intelligence, supported by instructional designs that emphasize ways of thinking, ways of working, mastery of tools for working, and understanding life in the world. These include citizenship at local and global levels, career and life skills, and personal and social responsibility. The conclusion highlights that optimizing students’ potential through multiple intelligences in 21st-century learning enables the achievement of six key competencies: communication, critical thinking, collaboration, creativity, connectivity, and character education with cultural awareness.